Interaction Ritual and Industrial Conflicts - Sutinah, Dra. (Advances in Social Sciences Research Journal, 2015)
This study examined industrial conflicts in East Java from the perspective of Randal Collins’ theory of interaction ritual. In particular, it looked at interaction ritual between labors and employers, members and committeee of labor unions, and inter-labor unions after the New Order, and attempted to explain the significance of industrial conflicts among labors. In the post-New order era considered more democratic, the interaction rituals between labors and employers have not been effective. The ineffectiveness of the rituals could produce suspicion, lack in the spirit of work, and no sense of belonging, causing conflicts between the labors and employers. In addition, while freedom of establishing unions is considered democratic, it can also make labors disintegrated becuse the more the unions, the tighter the competition in recruting the member. Horizontal conflicts are likely to coccur as the labor unions also become exclussive and more concerned with their own interests, which then makes the negotiation capability and orgnizations of the labors become weak. Their bargaining position is also getting weaker since the number of labors who join unions becomes smaller as a result of the increased number of outsourcing workers. Another consequence is that each labor activist has different interpretation of industrial conflict. Some view it as a measure of last resort to press the employers, and some other see it an arena of learning and struggling for labors’ normative rights.